APPLICATION OF COOPERATIVE LEARNING MODEL TYPE TGT THROUGH PLAYING TECHNIQUES TO INCREASE INTEREST AND PHYSICS LEARNING RESULTS STUDENTS - Budi Asih , Mundilarto (Universitas negeri Yogyakarta, 2018)
Abstrak Penelitian ini bertujuan untuk menerapkan langkah-langkah model pembelajaran kooperatif tipe TGT melalui teknik bermain, meningkatkan minat dan hasil belajar fisika dengan menggunakan model pembelajaran kooperatif tipe TGT (Teams Games Tournaments) melalui teknik bermain. Penelitian ini termasuk jenis Penelitian Tindakan Kelas. Desain penelitian menggunakan model Kemmis dan Mc Taggart. Teknik pengumpulan data menggunakan tes, observasi, dan angket. Teknik analisis data menggunakan analisis deskriptif secara persentase. Hasil penelitian menunjukkan bahwa hasil belajar fisika peserta didik kelas X MIPA 1 di SMA N 1 Pundong dapat ditingkatkan menggunakan model pembelajaran kooperatif tipe TGT melalui teknik bermain. Tindakan siklus I, peserta didik yang mencapai ketuntasan 15 siswa (50%). Tindakan siklus II, peserta didik yang mencapai KKM sebanyak 25 (93%). Siklus III, sebanyak 25 peserta didik (92,6%) telah mencapai KKM. Penurunan terjadi karena jumlah soal pada siklus III lebih sedikit sehingga persentase menjawab salah menjadi lebih besar. Kata kunci: Model pembelajaran kooperatif tipe Teams Games Tournaments, teknik bermain Abstract The aims of this study is to determine the steps of cooperative learning model type TGT (Teams Games Tournaments) through play techniques effectively, increase the interest and improve the physics learning results by applying cooperative learning model type TGT (Teams Games Tournaments) through playing technique. This study include the type of classroom action research. The research design is using Kemmis and Mc Taggart model. Data collection techniques used tests, observations, and questionnaires. The technique of data analysis using descriptive analysis in percentage. The results showed that physics learning results of students of class X MIPA 1 in SMA N 1 Pundong can be improved using cooperative learning model type Teams Games Tournaments (TGT). After the first cycle of action, students who achieve the completeness of 15 students (50%).After the second cycle of action, students who reach KKM as many as 25 (93%). Cycle III, as many as 25 students (92,6%) reached KKM. The decrease occurs because the number of questions in cycle III is less than the previous cycle so that the percentage of false become greater than previous. Keywords: Cooperative learning model type Teams Games Tournaments, play techniques